A conserved motif promotes HpaB‐regulated export of type III effectors from Xanthomonas. (16th October 2018) - Prochaska, Heike; Thieme, Sabine; Daum, Sebastian; Grau, Jan; Schmidtke, Cornelius; Hallensleben, Magnus; John, Peter; Bacia, Kirsten; Bonas, Ulla
Summary: The type III secretion (T3S) system, an essential pathogenicity factor in most Gram‐negative plant‐pathogenic bacteria, injects bacterial effector proteins directly into the plant cell cytosol. Here, the type III effectors (T3Es) manipulate host cell processes to suppress defence and establish appropriate conditions for bacterial multiplication in the intercellular spaces of the plant tissue. T3E export depends on a secretion signal which is also present in 'non‐effectors'. The latter are secreted extracellular components of the T3S apparatus, but are not translocated into the plant cell. How the T3S system discriminates between T3Es and non‐effectors is still enigmatic. Previously, we have identified a putative translocation motif (TrM) in several T3Es from Xanthomonas campestris pv. vesicatoria ( Xcv ). Here, we analysed the TrM of the Xcv effector XopB in detail. Mutation studies showed that the proline/arginine‐rich motif is required for efficient type III‐dependent secretion and translocation of XopB and determines the dependence of XopB transport on the general T3S chaperone HpaB. Similar results were obtained for other effectors from Xcv . As the arginine residues of the TrM mediate specific binding of XopB to cardiolipin, one of the major lipid components in Xanthomonas membranes, we assume that the association of T3Es to the bacterial membrane prior to secretion supports type III‐dependent export.